A generalization of operator stochastic integrals - Gorbunov, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We generalize the method for construction of operator stochastic integrals suggested by Berezanskii, Zhernakov, and Us. We extend the class of integrable commutative quantum processes and study properties of corresponding integrals.